1997
DOI: 10.1164/ajrccm.155.3.9117032
|View full text |Cite
|
Sign up to set email alerts
|

Tris-hydroxymethyl aminomethane and sodium bicarbonate to buffer metabolic acidosis in an isolated heart model.

Abstract: Metabolic acidosis induces a decrease in the developed force of cardiac muscle by affecting every step of the excitation--contraction coupling pathway. Due to transient worsening in intracellular acidosis, the value of administering sodium bicarbonate therapeutically during acute acidosis has been questioned. An alternative therapeutic drug, Tris-hydroxymethyl aminomethane (THAM) has the advantage of diffusing into the intracellular space. This study was designed to evaluate the effects of metabolic acidosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…There is strong animal data suggesting the many potential benefits of hypercapnic acidosis (3,11,22,24), recently augmented by secondary analysis of the ARDSNet data (12). On the other hand, skepticism persists among some, with experimental and clinical data touting drawbacks to hypercapnic acidosis (16) and benefits of various buffering strategies (17,23,28), with some compelling clinical arguments for the use of THAM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong animal data suggesting the many potential benefits of hypercapnic acidosis (3,11,22,24), recently augmented by secondary analysis of the ARDSNet data (12). On the other hand, skepticism persists among some, with experimental and clinical data touting drawbacks to hypercapnic acidosis (16) and benefits of various buffering strategies (17,23,28), with some compelling clinical arguments for the use of THAM.…”
Section: Discussionmentioning
confidence: 99%
“…Bicarbonate buffers react to liberate carbon dioxide, which, because of high membrane permeability, may raise concern for further intracellular acidosis (9), a potentially operative, although unproven, mechanism in studies demonstrating worsened lung barrier function with buffering of hypercapnic acidosis (13,18). Tris-hydroxymethyl aminomethane (THAM), acting as a proton acceptor independent of carbon dioxide pathways, has been shown in animal and clinical models to reverse cardio-depressant effects attributed to hypercapnic acidosis (21,23,28).…”
mentioning
confidence: 99%
“…Animals were randomly allocated to three groups (n = 7 per group): (1) normocapnia (NC) -mechanically ventilated as described above to maintain PaCO 2 between 35 and 45 mmHg; (2) hypercapnia (HC) -mechanically ventilated with a gas mixture containing 5% CO 2 , 21% O 2 , and balanced N 2 (Linde Gas Therapeutics, Lidingö, Sweden) to maintain PaCO 2 between 60 and 70 mmHg; and (3) buffered hypercapnia (BHC) -mechanically ventilated with a gas mixture containing 5% CO 2 , 21% O 2 , and balanced N 2 (Linde Gas Therapeutics, Lidingö, Sweden) to maintain PaCO 2 between 60 and 70 mmHg. After 5 min, a bolus of sodium bicarbonate solution (8.4%) was given intravenously equivalent to one-third of the dose calculated according to the following equation: HCO 3 − (mEq) = 0.3 × weight (kg) × base excess (BE) (Sirieix et al, 1997). The remaining seven animals were not mechanically ventilated (NV) and were used for measurement of lung histology and molecular biology analysis (Fig.…”
Section: Animal Preparation and Experimental Protocolmentioning
confidence: 99%
“…In isolated animal hearts perfused with acidic solutions, bicarbonate fails to augment ventricular contractility (70,82). In whole animals, the studies uniformly showed increased PaCO 2 and decreased pHi in different organs (62,83), augmented production of lactic acid (61,62,84), and failed to reveal any hemodynamic benefit for sodium bicarbonate when compared with iso-osmolar saline solution, regardless the extracellular pH and lactate concentrations (61,62,84,85).…”
Section: Rationalementioning
confidence: 99%